Treatment adherence in individuals with cystic fibrosis: An Observational Study: Treatment adherence in individuals with cystic fibrosis - Fontelle, Fernanda; VIEIRA, LUCAS; FAIÇAL, ADRIANA; BRAZIL, JULIANA; TEIXEIRA, MARCIA; SOUZA, EDNA LUCIA (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2026)
Introduction: Low treatment adherence is a complex issue frequently observed in cystic fibrosis (CF) patients. Objective: To evaluate the self-reported treatment adherence rate and the rate determined based on pharmacy medication dispensation records in individuals with CF, and to investigate the association between treatment adherence and sociodemographic variables. Methods: Cross-sectional study with a consecutive sample was conducted in a CF referral center in the Northeast of Brazil. Using two methods: (1) The Morisky-Green test measured the self-reported treatment adherence for pancreatin, dornase alfa, and inhaled tobramycin; (2) dispensation records of prescribed drugs. A medication usage percentage ≥ 80% was classified as good treatment adherence. Prevalence ratios were used to assess associations between good treatment adherence and studied variables. Results: Forty-two individuals were included, 55.8% female, median age 7.3 years. Self-reported good treatment adherence for the use of pancreatin, dornase alfa, and inhaled tobramycin were 65.8%, 50.0%, and 44.4% of the participants, respectively. According to pharmacy records, the percentages of good treatment adherence were 71.4%, 66.7%, and 52.6% for the use of dornase alfa, tobramycin, and pancreatin, respectively. When comparing the methods, the agreement in treatment adherence rates for medication use ranged from 64.0% to 85.7%. Conclusion: Treatment adherence was low and varied by medication and methodology. Good adherence was mainly associated with younger age and the lower-level education of caregivers.